Can the Cytokine Profile According to ABO Blood Groups Be Related to Worse Outcome in COVID-19 Patients? Yes, They Can - Tamayo-Velasco, Álvaro; Peñarrubia Ponce, María Jesús; Álvarez, Francisco Javier; Gonzalo-Benito, Hugo; de la Fuente, Ignacio; Pérez-González, Sonia; Rico, Lucía; Jiménez García, María Teresa; Sánchez Rodríguez, Alba; Hijas Villaizan, Milagros; Martín-Fernández, Marta; Dueñas, Carlos; et al. (Frontiers in Immunology, 2021)
Severe status of COVID-19 is extremely associated to cytokine release. Moreover, it has been suggested that blood group is also associate with the prevalence and severity of this disease. However, the relationship between the cytokine profile and blood group remains unclear in COVID-19 patients. In this sense, we prospectively recruited 108 COVID-19 patients between March and April 2020 and divided according to ABO blood group. For the analysis of 45 cytokines, plasma samples were collected in the time of admission to hospital ward or intensive care unit and at the sixth day after hospital admission. The results shown that there was a risk more than two times lower of mechanical ventilation or death in patients with blood group O (Log Rank: p=0.042). At first time, all statistically significant cytokine levels, except from hepatocyte growth factor, were higher in O blood group patients meanwhile the second time showed significant drop, between 20 and 40%. In contrast, A/B/AB group presented a maintenance of cytokine levels during time. Hepatocyte growth factor showed significant association with intubation or mortality risk in non-O blood group patients [OR: 4.229, CI 95% (2.064-8.665), p<0.001] and also was the only one bad prognosis biomarker in O blood group patients [OR: 8.852, CI 95% (1.540-50.878), p=0.015]. Therefore, higher cytokine levels in O blood group are associated with a better outcome than A/B/AB group in COVID-19 patients.